Successful on-pump surgery for treatment of a life threatening cardiopulmonary oncologic mass. Issue 11 (2015) - Queron, Sébastien; Ruyssevelt, Patrick Van; Beauduin, Marc; Penny, Marie-Odile; Obbergh, Luc Van; M, Servais; wijtenburg, Edo; Coulic, Very
No abstract available